Impact of the COVID-19 pandemic on psychotropic medication uptake: time-series analysis of a population-wide cohort. (December 2022) - Maguire, Aideen; Kent, Lisa; O'Neill, Siobhan; O'Hagan, Denise; O'Reilly, Dermot
Abstract : Background: The COVID-19 pandemic and associated lockdowns were predicted to have a major impact on mental health, however current studies have produced contradictory findings with limited longitudinal data. Aims: Nine years of linked, individual-level administrative data were used to examine changes in psychotropic medication uptake before and during the pandemic. Method: Medication data from a population-wide prescribing database were linked to demographic and socioeconomic indicators from healthcare registration records ( n = 1 801 860). Monthly prescription uptake was split (pre-restrictions: January 2012 to February 2020 and during restrictions: March to October 2020). Auto regressive integrated moving average (ARIMA) models were trained in R taking into consideration trends and seasonal effects. Forecast ('expected') monthly values were compared with 'actual' values, stratified by demographic factors. Results: Over the study period 38.5% of the study population were in receipt of ≥1 psychotropic medication. Uptake of these medications have been following a strong upward trend since January 2012. In March 2020 uptake of all medications increased beyond expected values, returning to expected trends from May 2020 for antidepressants, anxiolytics and antipsychotics. In the 8 months during restrictions uptake of hypnotic medication was 12% higher than expected among those <18 years, and anxiolytic medication higher than expected in those >65 years. Conclusions: Results suggest an initial 'stockpiling' of medications in March 2020 before trends mostly returned to expected levels. The anticipated tsunami of mental ill health is not yet manifest in psychotropic medication uptake. There are indications of increased anxiety and sleep difficulties in some subgroups, although these conditions may resolve as we emerge from the pandemic without need for psychiatric intervention.